Herramientas tecnológicas al servicio de la gestión empresarial (2010)
Information and communications technologies ICT’s are technological tools that allow companies of any industrial sector to gain operational improvements and increases the performance in all company areas in which such technologies have an important role. This paper makes a review of the more important information and communication technologies applied to companies management and making a characterization of such technologies in four main branches, with the purpose of improving the technology identification and selection process, which really can produce several activities improvements in Colombian companies.